Metrology - Gao, Wei.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The aim of this handbook is to provide a comprehensive summary of sensing and measurement in precision manufacturing, which is essential for process and quality control. The importance of precision sensing and measurements lies not only in the ability to distinguish whether the manufactured part meets the assigned tolerances through inspection but also, in many cases, reduce the deviation of the manufactured part from the designed values through improvement of the process or compensation manufacturing based on the sensing and measurement results. The information provided in the book will be of interest to industrial practitioners and researchers in the field of precision manufacturing sensing and measurements. This volume is part of a multi-volume handbook series that covers a comprehensive range of scientific and technological matters in 'Precision Manufacturing', for more information please view this link- https://www.springer.com/series/15575.
Process Sensing Technologies for Precision Manufacturing Process Control -- Precision Sensors for Length and Angle -- Measuring Instruments for Surface Forms -- Surface Finish Measuring Machines -- Large-Scale Measurement -- Microstructure Measurement -- Nano-Metrology -- Error Motion Measurement of Precision Machines -- Thermal Measurement and Compensation -- In-Process and On-Machine Measurement -- Inspection of Internal Defects using industrial NDT methods.
Keywords: Manufactures; Measurement; Measuring instruments; Surfaces (Technology).; Thin films; Microtechnology; Microelectromechanical systems; Machines, Tools, Processes; Measurement Science and Instrumentation; Surfaces, Interfaces and Thin Film; Microsystems and MEMS